1994
DOI: 10.1093/nar/22.11.2028
|View full text |Cite
|
Sign up to set email alerts
|

The heterodimeric subunit SRP9/14 of the signal recognition particle functions as permuted single polypeptide chain

Abstract: The targeting of nascent polypeptide chains to the endoplasmic reticulum is mediated by a cytoplasmic ribonucleoprotein, the signal recognition particle (SRP). The 9 kD (SRP9) and the 14 kD (SRP14) subunits of SRP are required to confer elongation arrest activity to the particle. SRP9 and SRP14 form a heterodimer which specifically binds to SRP RNA. We have constructed cDNAs that encode single polypeptide chains comprising SRP9 and SRP14 sequences in the two possible permutations linked by a 17 amino acid pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 30 publications
3
47
0
Order By: Relevance
“…In mammalian SRP, the proteins SRP14 and SRP9 bind specifically and exclusively as a heterodimeric complex to the Alu portion of 7SL RNA (Strub & Walter, 1990)+ In S. cerevisiae, a homolog of the mammalian SRP14 protein, Srp14p, has been identified, whereas a homolog of the SRP9 protein has not (Brown et al+, 1994) suggesting that Srp14p alone, possibly as a homodimer, may bind scR1 RNA+ This hypothesis was further strengthened by the finding that the mammalian proteins SRP9 and SRP14 were, despite their primary sequence divergence, structurally homologous (Birse et al+, 1997) suggesting that the heterodimer may have evolved from a homodimeric protein+ To test whether Srp14p can bind S. cerevisiae SRP RNA, scR1 RNA, we synthesized the protein and the RNA in vitro+ Both genes, SRP14 and SCR1, were am-plified from the yeast genome and inserted into plasmids to allow their transcription by SP6 and T7 RNA polymerase, respectively (see Materials and Methods)+ The synthetic transcripts comprising the SRP14 coding region were used to program wheat germ extract for the synthesis of [ 35 S]-labeled Srp14p+ The translation reaction was then incubated with in vitro-synthesized biotinylated scR1 RNA and the RNA-bound protein separated from free protein with immobilized streptavidin+ The bound protein was displayed by SDS-PAGE and visualized by autoradiography+ Reproducibly, ;40% of [ 35 S]-labeled Srp14p was bound to scR1 RNA, whereas ,5% of the protein was bound to a control RNA (Fig+ 1)+ The control RNA (cRNA) represents a portion of the antisense strand of the murine SRP14 mRNA and was previously used as a negative control in RNA-binding assays with the mammalian SRP9/14 heterodimer (Bovia et al+, 1994)+ The observed binding efficiency of Srp14p is practically identical to that found for SRP9/14 binding to Alu RNA (Bui et al+, 1997)+ Furthermore, increasing the scR1 RNA concentration by 10-fold and varying the salt concentrations between 150 mM and 350 mM did not change the binding efficiency, indicating that the binding conditions were optimal (results not shown)+ In addition, we tested an RNA that was derived from an scR1 RNA gene lacking the most 59 adenosine residue (results not shown)+ It bound Srp14p with the same efficiency as scR1 RNA, demonstrating that the adenosine is dispensable for protein binding+…”
Section: Srp14p Binds As a Homodimeric Complex To Scr1 Rnamentioning
confidence: 99%
See 1 more Smart Citation
“…In mammalian SRP, the proteins SRP14 and SRP9 bind specifically and exclusively as a heterodimeric complex to the Alu portion of 7SL RNA (Strub & Walter, 1990)+ In S. cerevisiae, a homolog of the mammalian SRP14 protein, Srp14p, has been identified, whereas a homolog of the SRP9 protein has not (Brown et al+, 1994) suggesting that Srp14p alone, possibly as a homodimer, may bind scR1 RNA+ This hypothesis was further strengthened by the finding that the mammalian proteins SRP9 and SRP14 were, despite their primary sequence divergence, structurally homologous (Birse et al+, 1997) suggesting that the heterodimer may have evolved from a homodimeric protein+ To test whether Srp14p can bind S. cerevisiae SRP RNA, scR1 RNA, we synthesized the protein and the RNA in vitro+ Both genes, SRP14 and SCR1, were am-plified from the yeast genome and inserted into plasmids to allow their transcription by SP6 and T7 RNA polymerase, respectively (see Materials and Methods)+ The synthetic transcripts comprising the SRP14 coding region were used to program wheat germ extract for the synthesis of [ 35 S]-labeled Srp14p+ The translation reaction was then incubated with in vitro-synthesized biotinylated scR1 RNA and the RNA-bound protein separated from free protein with immobilized streptavidin+ The bound protein was displayed by SDS-PAGE and visualized by autoradiography+ Reproducibly, ;40% of [ 35 S]-labeled Srp14p was bound to scR1 RNA, whereas ,5% of the protein was bound to a control RNA (Fig+ 1)+ The control RNA (cRNA) represents a portion of the antisense strand of the murine SRP14 mRNA and was previously used as a negative control in RNA-binding assays with the mammalian SRP9/14 heterodimer (Bovia et al+, 1994)+ The observed binding efficiency of Srp14p is practically identical to that found for SRP9/14 binding to Alu RNA (Bui et al+, 1997)+ Furthermore, increasing the scR1 RNA concentration by 10-fold and varying the salt concentrations between 150 mM and 350 mM did not change the binding efficiency, indicating that the binding conditions were optimal (results not shown)+ In addition, we tested an RNA that was derived from an scR1 RNA gene lacking the most 59 adenosine residue (results not shown)+ It bound Srp14p with the same efficiency as scR1 RNA, demonstrating that the adenosine is dispensable for protein binding+…”
Section: Srp14p Binds As a Homodimeric Complex To Scr1 Rnamentioning
confidence: 99%
“…The RNA-binding experiments have previously been described in Bui et al+ (1997)+ Instead of streptavidin-coated agarose beads, we used Streptavidin Dynabeads M-280 (Dynal A+S+, Oslo, Norway) in the binding assays+ The binding reactions were carried out in 20 mL containing 5 mL translation reactions and 1 mL of 1 mM biotinylated RNA (or higher concentration when indicated), 100 ng/mL competitor tRNA (50 ng/mL tRNA of E. coli and approximately 50 ng/mL calf liver tRNA from the translation reaction), 150 mM potassium acetate (or 350 mM), 1+5 mM magnesium acetate (or 3+5 mM), 50 mM N-2-hydroxyethyl piperazine-N9-2-ethanesulfonic acid/ potassium hydroxide (HEPES/KOH), pH 7+5, 1 mM dithiothreitol (DTT), 0+01% Nikkol (Nikko Chemical, Tokyo, Japan)+ After incubations of 10 min on ice and 10 min at 26 8C, the reactions were added to 20 mL of the same buffer containing 0+1% Triton X-100 and 12 mL Streptavidin beads that were previously equilibrated in the same buffer+ At higher RNA concentrations (0+15 or 0+5 nM), 20 mL of Streptavidin beads were used in the binding reactions+ After 20 min incubation with the beads, they were washed three times for 5 min with 200 mL of the same buffer+ To prepare glycerol step gradients, 150 mL each of 25, 20, 15, and 10% glycerol solutions in 350 mM potassium acetate, 3+5 mM magnesium acetate, 50 mM HEPES/KOH, pH 7+5, 1 mM DTT, and 0+01% Nikkol were overlaid and left in the cold for 2 h+ PhySrp14p and Rycom188 RNA (30 pmol each) were combined in the same buffer and incubated on ice and at 26 8C for 10 min each before layering on top of the gradient+ Gradients were run overnight at 4 8C at 40,000 rpm in a TST 55+5 ultracentrifuge rotor+ The gradients were collected in six fractions, of which 20% was used for the analysis of the RNA and 40% each for the analysis of the protein and for the cross-linking experiments+ The RNA was analyzed after phenol/dichloromethane extraction and ethanol precipitation in the presence of 1 mg carrier tRNA from E. coli on a 8% denaturing polyacrylamide gel and visualized with Gelstarா+ Cross-linking was done as described previously (Bovia et al+, 1994) with 0+08% glutaraldehyde+ Proteins were precipitated with 10% final concentration of trichloroacetic acid and analyzed by 15% SDS-PAGE and visualized with silver staining or, in the case of [ 35 S]-labeled proteins, with fluorography+…”
Section: Rna Binding Experimentsmentioning
confidence: 99%
“…How these motifs interact to bind RNA is presently unknown, possibly the role of these multiple RNA-binding sites is to anchor and to bend distant RNA elements. In SRP, the heterodimer SRP9/14 can be replaced by a fusion protein which comprises SRP9 and SRP14 in one single polypeptide chain without a loss in elongation arrest activity of the particle (Bovia et al, 1994). However, in vivo the two proteins exist as two separate entities, suggesting that the formation of homodimeric complexes might be important for their function in vivo.…”
Section: Srp Proteins: Members Of Ancient Nucleic Acid-binding Foldsmentioning
confidence: 99%
“…Furthermore, the human SRP14 is larger than its murine counterpart, this difference being due to a C-terminal alanine/threonine-rich extension [25]. SRP9 can be highly over-expressed in Escherichia coli and is stable after purification [26]. SRP9 crystallization is described in the accompanying paper (Doubli6 et al).…”
Section: Introductionmentioning
confidence: 99%
“…SRP~14-9 can functionally replace the SRP9/14 heterodimeric subunit in the SRP. It binds SRP RNA and functions in elongation arrest and release of elongation arrest without loss of activity compared to the native SRP9/14 heterodimer [26]. Two constructions of the fusion protein SRPOl4-9 and SRPO9-14, differing in the order of arrangement of SRP9 and SRP14 in the polypeptide, have been shown to be equally active, indicating that the free N-or C-termini in either protein, SRP9 or SRP14, are not essential structural elements in the function of the SRP9/14 heterodimer in the SRP.…”
Section: Introductionmentioning
confidence: 99%